1995
DOI: 10.1227/00006123-199511000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Brain Lesions in the First 12 Hours after Head Injury

Abstract: From January 1, 1990, to April 30, 1994, 412 patients were admitted to our intensive care unit in coma after head injuries. Our study group consisted of 37 patients who were retrospectively identified as harboring lesions or developing new lesions within a 12-hour period from the time of admission. We defined the evolution of a lesion as an increase or decrease in the size of an already present hematoma or as the appearance of a totally new lesion. There were 25 male and 12 female patients (mean age, 34.9 yr),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(53 citation statements)
references
References 27 publications
4
47
0
2
Order By: Relevance
“…Such injuries are characterized by mechanical damage to the parenchyma and its vasculature, resulting in sub-sequent hemorrhage and edema formation. Although clotting may constrain hemorrhage soon after injury, there is considerable evidence to suggest that persistent bleeding can occur in the early hours post-trauma (Servadei et al, 1995;Oertel et al, 2002;Chang et al, 2006;Chieregato et al, 2005;Lobato et al, 1991). Current management of tICH focuses on the identification and surgical evacuation of lesions large enough to generate mass effect and likely result in further neurological deterioration (Bullock et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Such injuries are characterized by mechanical damage to the parenchyma and its vasculature, resulting in sub-sequent hemorrhage and edema formation. Although clotting may constrain hemorrhage soon after injury, there is considerable evidence to suggest that persistent bleeding can occur in the early hours post-trauma (Servadei et al, 1995;Oertel et al, 2002;Chang et al, 2006;Chieregato et al, 2005;Lobato et al, 1991). Current management of tICH focuses on the identification and surgical evacuation of lesions large enough to generate mass effect and likely result in further neurological deterioration (Bullock et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In other study of Zumkeller et al, survival rate was reported as 50% in comatose patients with 18 mm subdural hematoma thickness and 20 mm middle line shift (18). In a study of Servadei et al, sizes of lesions decreased in 15 of 37 patients in first 12 hours while 22 showed increase in lesion sizes (19). In this study, in contrast to the literature, changes in hemorrhage thickness of CT (between zero and 23 mm) did not affect the operation-non-operation decision and the progression process with and without sequelae of patients.…”
Section: Discussionmentioning
confidence: 89%
“…7 These 37 patients represented 9% of all severe head injury patients. Of these patients, only 22 patients (5%) had lesions that worsened from their initial scan.…”
Section: Researching Clinical Recommendationsmentioning
confidence: 99%